The Meaning of Bhanti-Bhanti as Learning Media for Early Childhood in Wakatobi - Udu, Sumiman; Jumaidin, La Ode; Ibrahim, Irianto; Marwati, Marwati; Susanto, Aris (el Harakah: Jurnal Budaya Islam, 2023)
The "lunga-lunga" tradition is a custom of putting a baby to sleep by lying on a pillow placed on the shins of the feet while chanting the traditional "bhanti-bhanti" as musical accompaniment. In this "bhanti-bhanti" text, the mother expresses all cultural values to her child. This research used an ethnographic paradigm to explore the education values and the cultural learning from the “bhanti-bhanti’ practiced in Wakatobi. Thus, data collection and processing were carried out using the principles of the ethnographic paradigm. It was found that this tradition is a custom of learning various cultural values that exist in the Wakatobi community. The teaching content consists of moral values, explaining history, and building hope for children. A mother creates sacred texts and simultaneously builds hope about the importance of education, including morals in the family, environment, and social life. Another lesson is to instill the value that "it is better to be hungry than to eat food that is not rightfully yours." Lastly, "bhanti-bhanti" in the "lunga-lunga" tradition teaches cultural values that can contribute to the formation of children from an early age. Tradisi “lunga-lunga” merupakan pranata menidurkan bayi dengan cara berbaring di atas bantal yang diletakkan di atas tulang kering kaki sambil melantunkan lagu adat “bhanti-bhanti” sebagai musik pengiringnya. Dalam teks “bhanti-bhanti” ini, ibu mengungkapkan segala nilai budaya kepada anaknya. Penelitian ini menggunakan paradigma etnografi untuk mengulas nilai Pendidikan dan pembelajaran budaya dari “bhanti-bhanti” yang diterapkan di Wakatobi. Dengan demikian pengumpulan dan pengolahan data dilakukan dengan menggunakan prinsip paradigma etnografi. Diketahui bahwa tradisi “lunga-lunga” merupakan tradisi pembelajaran berbagai nilai budaya yang ada pada masyarakat Wakatobi. Isi pengajarannya terdiri dari nilai-nilai moral, menjelaskan sejarah, dan membangun harapan bagi anak. Seorang ibu menciptakan teks-teks suci dalam waktu dan ruang yang sama, membangun harapan akan pentingnya pendidikan, termasuk akhlak dalam keluarga, lingkungan, dan kehidupan bermasyarakat. Hikmah lainnya adalah dengan menanamkan nilai bahwa “lebih baik lapar daripada makan makanan yang bukan haknya”. Terakhir, “bhanti-bhanti” dalam tradisi “lunga-lunga” mengajarkan nilai-nilai budaya yang dapat memberikan kontribusi dalam pembentukan anak sejak dini.